Module 9. Integration by Trigonometric Substitution
Module 9. Integration by Trigonometric Substitution
DIFFUN CAMPUS
Diffun, 3401 Quirino
Prepared by
𝑎 √𝑎2 + 𝑢2 𝑢
𝑢 𝑢 √𝑢2 − 𝑎2
√𝑎2 − 𝑢2 𝑎 𝑎
√9−4𝑥 2
Illustration 1. Evaluate ∫ 𝑑𝑥`
𝑥
𝑎2 = 9 𝑢2 = 4𝑥 2
𝑎=3 𝑢 = 2𝑥
These values will replace the variables in 𝑢 = 𝑎 sin 𝜃. Thus,
QUIRINO STATE UNIVERSITY
DIFFUN CAMPUS
Diffun, 3401 Quirino
√9−4𝑥 2 √9−9𝑠𝑖𝑛2 𝜃 3
∫ 𝑑𝑥 = ∫ 3 ( cos 𝜃 𝑑𝜃) By substitution
𝑥 sin 𝜃 2
2
√9(1−𝑠𝑖𝑛2 𝜃)
= ∫ (cos 𝜃 𝑑𝜃) Simplify the integrand
sin 𝜃
√9 𝑐𝑜𝑠 2 𝜃
= ∫ (cos 𝜃 𝑑𝜃)
sin 𝜃
𝑐𝑜𝑠 2 𝜃 𝑑𝜃
= 3∫ Use the relation
sin 𝜃
𝑐𝑜𝑠 2 𝜃 = 1 − 𝑠𝑖𝑛2 𝜃
1−𝑠𝑖𝑛2 𝜃
= 3∫ 𝑑𝜃 Simplify the integrand using
sin 𝜃
trigo. identities
= 3 ∫ csc 𝜃 𝑑𝜃 − 3 ∫ sin 𝜃 𝑑𝜃 Distributive property
2𝑥
From 2𝑥 = 3 sin 𝜃; sin 𝜃 =
3
3 √9−4𝑥 2 √9−4𝑥 2
csc 𝜃 = ; cot 𝜃 = ; cos 𝜃 =
2𝑥 2𝑥 3
2𝑥 3
𝜃
√9 − 4𝑥 2
3 √9−4𝑥 2 √9−4𝑥 2
3 ln(csc 𝜃 − cot 𝜃) − 3 cos 𝜃 + 𝐶 = 3 ln ( − )−3( )+ 𝐶
2𝑥 2𝑥 3
3
3−√9−4𝑥 2
= ln ( 2𝑥
) − √9 − 4𝑥 2 + 𝐶 ∎
𝑑𝑥
Illustration 2. Evaluate ∫
𝑥 4 √4𝑥 2 −1
Solution: The radical in the integrand takes the form of √𝑢2 − 𝑎2 , so the proper
substitution is letting 𝑢 = 𝑎 sec 𝜃. Then, by correspondence
𝑢2 = 4𝑥 2 𝑎2 = 1
𝑢 = 2𝑥 𝑎=1
1 4 1
Let 𝑢 = 𝑎 sec 𝜃 For 𝑥 4 : 𝑥 4 = ( sec 𝜃) = 𝑠𝑒𝑐 4 𝜃
2 16
1
𝑑𝑥 sec 𝜃 tan 𝜃 𝑑𝜃
2
∫ 𝑥4 √4𝑥2 −1 = ∫ 1 By substitution
𝑠𝑒𝑐 4 𝜃√𝑠𝑒𝑐 2 𝜃−1
6
tan 𝜃 𝑑𝜃
= 8∫ Simplify the radicand
𝑠𝑒𝑐 3 𝜃√𝑡𝑎𝑛2 𝜃
𝑑𝜃 1
= 8 ∫ sec3 𝜃 Apply reciprocal identity sec 𝜃 =
cos 𝜃
From 2𝑥 = sec 𝜃
2𝑥
√4𝑥 2 −1
sin 𝜃 = √4𝑥 2 − 1
2𝑥
𝜃
1
3
8 3 √4𝑥2 −1 8 √4𝑥2 −1 √4𝑥 2 −1
8 sin 𝜃 − 3 𝑠𝑖𝑛 𝜃 + 𝐶 = 8 ( 2𝑥
)−
3
(
2𝑥
) +𝐶 Replace sin 𝜃 by
2𝑥
3
4√4𝑥 2−1 (√4𝑥 2 −1)
=
𝑥
− 3𝑥 3
+𝐶 or
√4𝑥 2 −1
(1 + 3𝑥 − 4𝑥 2 ) + 𝐶 ∎
3𝑥 2
√𝑥 𝑑𝑥
Illustration 3. ∫ (𝑥+1)3
Solution: In this case the integrand takes the form (𝑎2 + 𝑢2 )𝑛 , so we will use
𝑢 = 𝑎 tan 𝑢 for our substitution.
𝑢2 = 𝑥 𝑎2 = 1
𝑢 = √𝑥 𝑎=1
𝑡𝑎𝑛2 𝜃𝑠𝑒𝑐 2 𝜃 𝑑𝜃
= 2∫ (𝑠𝑒𝑐 2 𝜃)3
Simplify the integrand
𝑡𝑎𝑛2 𝜃 𝑑𝜃
= 2∫ 𝑠𝑒𝑐 4 𝜃
Express the trigo. functions in terms of sin 𝜃 and
cos 𝜃
QUIRINO STATE UNIVERSITY
DIFFUN CAMPUS
Diffun, 3401 Quirino
𝑠𝑖𝑛2 𝜃
𝑐𝑜𝑠2 𝜃
= 2∫ 1 𝑑𝜃
𝑐𝑜𝑠4 𝜃
1−cos 2𝜃 1+cos 2𝜃
= 2∫( )( ) 𝑑𝜃 Multiply the integrand
2 2
1
= 2
∫(1 − 𝑐𝑜𝑠 2 2𝜃 )𝑑𝜃
1 1
= 2
∫ 𝑑𝜃 − 2 ∫ 𝑐𝑜𝑠 2 2𝜃 𝑑𝜃 using trigo. transformation on the 2nd
integral
1 1 1+cos 4𝜃
= ∫ 𝑑𝜃 − 2 ∫ ( ) 𝑑𝜃
2 2
1 1 1
= ∫ 𝑑𝜃 − 4 ∫ 𝑑𝜃 − 4 ∫ cos 4𝜃 𝑑𝜃 Simplify
2
1 1 1
= ∫ 𝑑𝜃 − ∙ ∫ cos 4𝜃 (4𝑑𝜃)
4 4 4
1 1
= 𝜃− sin 4𝜃 + 𝐶 Redefine 𝑠𝑖𝑛 4𝜃 as
4 16
𝑠𝑖𝑛 4𝜃 = 2 sin 2𝜃 cos 2𝜃
1 1
= 𝜃 − 16 (2 sin 2𝜃 cos 2𝜃 ) + 𝐶 but sin 2𝜃 = 2 sin 𝜃 cos 𝜃;
4
cos 2𝜃 = 𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛 2 𝜃
1 1
= 𝜃 − 8 [(2 sin 𝜃 cos 𝜃 )(𝑐𝑜𝑠 2 𝜃 − 𝑠𝑖𝑛2 𝜃 )] + 𝐶
4
1 1
= 𝜃 − 4 [sin 𝜃 𝑐𝑜𝑠 3 𝜃 − 𝑠𝑖𝑛3 𝜃 cos 𝜃 ] + 𝐶
4
Replace 𝜃 in terms of 𝑥
From √𝑥 = tan 𝜃 ; 𝜃 = arctan √𝑥
√𝑥 1
√𝑥 + 1 sin 𝜃 = ; cos 𝜃 =
√𝑥+1 √𝑥+1
√𝑥
𝜃
1
3 3
1 1 √𝑥 1 √𝑥 1
= arctan √𝑥 − [ ∙( ) −( ) ∙( )] + 𝐶
4 4 √𝑥+1 √𝑥+1 √𝑥+1 √𝑥+1
1 1 √𝑥 𝑥 √𝑥
= arctan √𝑥 − [(𝑥+1)2 − (𝑥+1)2 ] + 𝐶 Simplify
4 4
(1−𝑥)
= 14 arctan √𝑥 − 4(𝑥+1)√𝑥2 + 𝐶 ∎
√9−4𝑥 2
2. ∫ 𝑑𝑥
𝑥
𝑑𝑥
3. ∫
𝑥 4 √4𝑥 2 −1
QUIRINO STATE UNIVERSITY
DIFFUN CAMPUS
Diffun, 3401 Quirino
𝑑𝑥
4. ∫ 2 2 3⁄2
(𝑎 +𝑥 )
25 𝑥 1
1. 𝐴𝑟𝑐 sin ( ) − 𝑥√25 − 𝑥 2 + 𝐶
2 5 2
3
3−√9−4𝑥 2
2. ln ( ) + √9 − 4𝑥 2 + 𝐶
2𝑥
𝑥√𝑎2 +𝑥 2
4. +𝐶
𝑎2 (𝑎2+𝑥 2 )